AKSIOLOGI SPIRITUALITAS DALAM KONSELING - Gudnanto Gudnanto; Cindy Asli Pravesti; Fitri Wahyuni; Arista Kiswantoro (JURNAL KONSELING GUSJIGANG, 2017)
Human beings are the highest in rank than other god creatures. Why is that?, of course the answer is because human beings have been given by the intellect and mind that can make men appear as a vicegerent on earth. Every human being has a belief in something that is considered supreme or sovereign. Confidence is what is called spiritual. Axiology is the branch of philosophy that studies the nature of value. Based on its main staple axiology can be divided into Ethics (philosophy of good bad human behavior) or moral philosophy and aesthetics or philosophy of magnificence. Many people feel has reached a goal or reach the pinnacle of success both career and matter, but felt something "hollow and empty". Generally, they realized that they had to climb the stairs wrong, even after they reach the top rung of his career. It turns out in the end, Money, Possessions, Honorary, and the notch is not a "thing" that they are looking for. Successful people are obviously people were very helpful both socially and economically for the company, but lost "Spiritual meaning" in itself. Such diseases suffered by many modern people, who are often called Spiritual Pathology or Spiritual illness. Axiology spirituality in Counseling is the help given by individuals (in this case the support is a counselor) to another individual (counselee) in order to find the values of ethics and aesthetics of the existence of happiness essentials (holy) is the happiness that comes from the Almighty (God).